Effect of Betel Leaf (Piper sp.) Water Extracts to Control Penicillium digitatum Causes of Green Mold in Dekopon Citrus (Citrus reticulata) - Ceppy Nasahi; Ria Aghaselly Clonelin (CROPSAVER, 2021)
Green mold disease (Penicillium digitatum Sacc.) is one of the main problems in citrus fruits. Some studies had made use of biopesticides in treating postharvest diseases. Some studies reported that plant extracts can suppress various pathogens caused to have antifungal characteristics. One of the plants that are widely used as an extract is green betel leaf (Piper betle) and red betel (Piper ornatum).. This study aims to determine the effect of water extracts from green betel leaf  and red betel leaf in suppressing P. digitatum in dekopon citrus (Citrus reticulata Shiranui). The experiment used the experimental method of Completely Randomized Design with 7 treatments and 3 replications. The results showed that the water extracts of green betel leaf and red betel can inhibit the pathogen P. digitatum both in vitro and in vivo. The red betel leaf water extract at concentration of 10% was able to inhibit the colony diameter of P. digitatum in vitro at 43.61% and green betel lef extract at concentration of 10%  was 39.34%. The best inhibition of green water extract and red betel the diameter of green mold disease on dekopon fruit was 15.95% and 39.74%, respectively. The water extracts of green betel leaf and the red betel leaf were able to inhibit green mold disease in vivo successively was 0.52-19.62% and 17.64-52.67%. The treatment of 10% green betel water extract was able to suppress the growth of green mold disease in dekopon fruit was 19.62% and 10% red betel water extract inhibition was 19.62%.